Perception .. and the presence of the forbidden in the Iraqi festive theatrical show (Journal of the College of Basic Education, 2023)
Summary of the research :The researcher pointed out, through the sum of the ceremonial theatrical works that he produced, some of the empty spaces that were contained in the theories of directing, which prompted him to diligently search to find a mechanism for performance in ceremonial theater performances different from what is prevalent. the actor. In order to add truth to this term, the researcher resorted to adopting dictionaries of Arabic grammar in fixing its definition and its connotations by referring it to its triple verb and then resorting to its derivative inflection according to the table of approved weights in the conjugation of verbs, leading to its idiomatic definition in the field of theater, and then coming up with its concept through application. Therefore, the research problem was presented in the following question:(What is the different technique to what is prevalent that helps the actor and director to reach the structure of the celebratory theatrical character)?While his goal has become to impart truthfulness to the term (perception) as a new technique that helps the actor and director to revive the dramatic personality in the festive theatrical performance, then its importance in that it benefits researchers and scholars in the field of theater, and then defines the terms that were mentioned in the title of the research with mention The temporal, spatial and objective limits of the research. The theoretical framework was built on two topics, the first was titled Perception - Meaning and Concept - while the second came under the title Presence and Prohibition, where the researcher dealt with the concept of each of them and ended up fixing the indicators that resulted from the theoretical framework. Each moment, according to the data of the event, is a different personality than the one before or after it, and that the presence is material and moral, and the prohibitions are all labels that conflict with the concepts of religion, social norms, and political systems. In the research procedures, the researcher explained his research community, his sample, and the reasons for choosing it, then the research methodology and its tools, and thus the narration of the narrative structure of the presentation, and then his analysis. Finally, he reached a set of results that he discussed based on the indicators of the theoretical framework. Or incest or animals are among the most dangerous religious, social, customary and political prohibitions. After that, the researcher mentioned the most important conclusions, concluding his research with a list of sources and references.Keywords: perception - attendance - prohibited - festive play.